Single nucleotide polymorphism array analysis defines a specific genetic fingerprint for well-differentiated cutaneous SCCs. - Purdie, K; Harwood, C; Gulati, A; Chaplin, T; Lambert, SR; Cerio, R; Kelly, G; Cazier, J; Young, B; Leigh, I; Proby, C (2009)
Cutaneous squamous cell carcinomas (cSCCs) are the second most frequent cancers in fair-skinned populations; yet, because of their genetic heterogeneity, the key molecular events in cSCC tumorigenesis remain poorly defined. We have used single nucleotide polymorphism microarray analysis to examine genome-wide allelic imbalance in 60 cSCCs using paired non-tumor samples. The most frequent recurrent aberrations were loss of heterozygosity at 3p and 9p, observed in 39 (65%) and 45 (75%) tumors, respectively. Microdeletions at 9p23 within the protein tyrosine phosphatase receptor type D (PTPRD) locus were identified in 9 (15%) samples, supporting a tumor suppressor role for PTPRD in cSCC. In addition, microdeletions at 3p14.2 were detected in 3 (5%) cSCCs, implicating the fragile histidine triad (FHIT) gene as a possible target for inactivation. Statistical analysis revealed that well-differentiated cSCCs demonstrated significantly fewer aberrations than moderately and poorly differentiated cSCCs; yet, despite a lower rate of allelic imbalance, some specific aberrations were observed equally frequently in both groups. No correlation was established between the frequency of chromosomal aberrations and immune or human papillomavirus status. Our data suggest that well-differentiated tumors are a genetically distinct subpopulation of cSCC.